Anabolic deficiencies in men with systolic heart failure: do co-morbidities and therapies really contribute significantly?. (26th June 2013) - Kalicińska, Elżbieta; Wojtas, Katarzyna; Majda, Jacek; Doehner, Wolfram; Haehling, Stephan von; Banasiak, Waldemar; Ponikowska, Beata; Borodulin-Nadzieja, Ludmila; Anker, Stefan D.; Ponikowski, Piotr; Jankowska, Ewa A.
Abstract: Background : Deficiencies of anabolic hormones are common in men with heart failure (HF). It remains unclear whether the deranged metabolism of these hormones is the pathophysiological element of HF itself or is the consequence of co-morbidities or/and treatment in HF. Methods : We examined 382 men with systolic HF. Serum hormones (i.e. total testosterone [TT], DHEAS, IGF-1) were assessed using immunoassays, serum free testosterone (eFT) – using the Vermeulen equation. Results : Prevalence of TT and eFT deficiencies was similar in men with HF aged < versus ≥60 years (23% and 32% for TT and eFT deficiencies). Deficiencies in DHEAS and IGF-1 were more common in younger (63% and 92%) than older patients (48% and 73%). In men <60 years, TT deficiency was accompanied by the therapy with digoxin, eFT deficiency – the therapy with digoxin and the presence of diabetes, DHEAS deficiency – the therapy with loop diuretic (all p  < 0.05). In men ≥60 years, TT deficiency – the therapy with loop diuretic, DHEAS deficiency – the therapy with spironolactone and digoxin, and hsCRP, IGF-1 deficiency – the high hsCRP (all p  < 0.05). Conclusions : Deficiencies in anabolic hormones are common in younger and older men with HF. Some therapies (but not major co-morbidities) may contribute to anabolic deficiencies.